2015
DOI: 10.1128/aem.00762-15
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanism of Ferulic Acid Decarboxylase (FDC1) from Saccharomyces cerevisiae

Abstract: The nonoxidative decarboxylation of aromatic acids occurs in a range of microbes and is of interest for bioprocessing and metabolic engineering. Although phenolic acid decarboxylases provide useful tools for bioindustrial applications, the molecular bases for how these enzymes function are only beginning to be examined. Here we present the 2.35-Å-resolution X-ray crystal structure of the ferulic acid decarboxylase (FDC1; UbiD) from Saccharomyces cerevisiae. FDC1 shares structural similarity with the UbiD famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Phylogenetic analysis of the putative o ‐phthalyl‐CoA decarboxylase revealed that PhtDa (PA01_00217) was affiliated with UbiD‐like decarboxylases (Bhuiya et al , ) that are known to decarboxylate, for example 3‐polyprenyl‐4‐hydroxybenzoate in Escherichia coli (Baba et al ., ). UbiD‐like decarboxylases are commonly found in bacteria (Jacewicz et al ., ) and are involved in ubiquinone biosynthesis (Zhang and Javor, ).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis of the putative o ‐phthalyl‐CoA decarboxylase revealed that PhtDa (PA01_00217) was affiliated with UbiD‐like decarboxylases (Bhuiya et al , ) that are known to decarboxylate, for example 3‐polyprenyl‐4‐hydroxybenzoate in Escherichia coli (Baba et al ., ). UbiD‐like decarboxylases are commonly found in bacteria (Jacewicz et al ., ) and are involved in ubiquinone biosynthesis (Zhang and Javor, ).…”
Section: Discussionmentioning
confidence: 99%
“…These include species which represent contaminants in a brewing environment, but also species and strains utilized in brewing. Many strains of brewer's yeast (Saccharomyces cerevisiae), as well as Brettanomyces sp., Lactobacillus, and Pediococcus are PAD+ [50][51][52][53][54]. These non-Saccharomyces genera of microbes are utilized in traditional sour beers of Belgium, and increasingly in other "wild" and sour beer styles popular in the craft brewing industry [36,37,[39][40][41]50].…”
Section: Microbial Enzymatic Decarboxylation To Vinyl Derivativesmentioning
confidence: 99%
“…This "phenolic off-flavor" character requires two enzymes, a phenylacrylic acid decarboxylase (PAD1) and a ferulic acid decarboxylase (FDC1). Somewhat confusingly, the PAD1 enzyme is not a decarboxylase, but catalyzes the synthesis of an FMN-related co-factor required for the function of FDC1 [52,55]. FDC1 enzyme catalyzes the decarboxylation of cinnamic acid and derivatives.…”
Section: Microbial Enzymatic Decarboxylation To Vinyl Derivativesmentioning
confidence: 99%
See 2 more Smart Citations